Avocado pests and avocado trade - Peterson, Everett B.; Orden, David (Wiley, 2008)
This article evaluates the effects of a November 2004 phytosanitary rule that removed seasonal and geographic restrictions on the importation of fresh Hass avocados from approved orchards in Mexico to the United States. With the remaining systems approach compliance measures in place, pest risks do not substantially increase and U.S. net welfare rises by $77 million. Removal of remaining compliance measures may lead to lower net welfare gains depending on which measures are eliminated and the estimated probabilities of pest infestations.